Framing academic leadership positioning for the global university. - Jusoff, Kamaruzaman; Abu Samah, Siti Akmar (Academic Leadership, 2009)
The article focuses on framing academic leadership positioning for a global university in Malaysia. Adapting the business scenario, the models for global positioning in the external grounding involves organizational characteristics of three modes which are multinational, global and transnational. Academia need to develop strong sense of independence amongst its academic community and the use of collegial consultation process.